It is hereby performed-- : explorations in legal speech acts - Kurzon, Dennis (Amsterdam ; Philadelphia : J. Benjamins Pub. Co., 1986)
This book deals with speech acts, especially performatives, that are regarded as 'operative' in legal discourse. After a detailed exposition of speech act theory in relation to legislative texts, the author discusses the legal document as a communicative act; potential speech acts and delegated legislation; wills, the marriage ceremony and statutes as reversible performatives; and the distinction between the deictic function of this and the anaphoric function of that in legal documents. The final chapter is concerned with another text type, case reports, and addresses the questio.
3. POTENTIAL SPEECH ACTS: THE GRAMMAR OF DELEGATING POWER3.1. Introduction; 3.2. Features of potential speech acts; 3.3. Similar structures; 3.4. Wills and deeds; 4. REVERSIBLE PERFORMATIVES; 5. 'THIS' AND 'THAT' IN LEGAL TEXTS; 6. WHAT DOES A JUDGE DO'? SEMANTICS AND PRAGMATICS IN COURT JUDGMENTS; 6.1. Introduction; 6.2. Modality; 6.3. Conditionals; 6.4. Non-factive predicators; 6.5. Conclusion; FOOTNOTES; APPENDIX; REFERENCES
Includes bibliographical references (pages 77-81).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Law -- Language; Semantics (Law); Speech acts (Linguistics); Droit -- Langage; Sémantique (Droit); Actes de parole; LAW -- Essays; LAW -- General Practice; LAW -- Jurisprudence; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; LAW -- Reference; Law -- Language; Semantics (Law); Speech acts (Linguistics); Electronic book